Modeling Regional Seismic Waves - Helmberger, Donald V.; Harkrider, David G. (1992)
This research performed under the contract, during the period 26 September 1990 through 25 September 1991, can be divided into two main topics; determining compressional velocity by modeling waveforms and travel time data from long-period and short-period recordings and determining surface wave magnitudes for NTS events using regional datas. In section 1, we derive a compressional velocity model for the northwest Atlantic Ocean by modeling wave form and travel time data from long-period and short-period WWSSN and Canadian network station recordings. A ninety kilometer thick lid with the velocity of 8. 1 km/sec at the top gradually changing to 8.3 km/sec at the bottom is obtained by fitting the travel time data of first arrivals and waveform data of pure oceanic paths at distance of 8 - 20 degrees. Triplication P waveform data constrains the structure below the lid. A distinct low velocity zone is located at depth of about 170 km. Combining with the shear wave structure derived by Grand and Helmberger (1984a) for the same region, we can infer a very oliving- rich mineralogy in the upper 100 km and a very garnet - rich mineralogy at the depth of 200 - 400 km, at which partial melting should be also responsible for the very high VP/VS ratio. In section 2, we re-examine the use of surface wave magnitudes as a determination of yield of under-ground explosions and the associated magnitude-yield scaling relationship. We have calculated surface wave magnitudes for 190 Nevada Test Site (NTS) underground nuclear explosions from a data set of regional long-period seismograms from a combined super-network of 55 North American stations. Great effort went towards making the data set comprehensive and diverse in terms of yield, source location and shot medium in order to determine the portability of surface wave magnitude scales.